Political imperatives and military preparations: New insights into why South Africa's 1998 intervention in Lesotho went awry. Issue 1 (2nd January 2019) - Williams, Christopher
ABSTRACT: In September 1998 South African troops crossed into Lesotho to restore stability to the small mountain kingdom that had been roiled by protests for months. Operation Boleas encountered heavy resistance – in the ensuing chaos dozens died and the towns of Maseru, Mohale's Hoek and Mafeteng were damaged. Media and scholarly commentary on the intervention was scathing, but in the rush to judge there has been insufficient effort to chronicle and clarify. This article uses declassified archival records and interviews with policy makers to provide a more exhaustive explanation of how the Mandela Administration decided on the deployment of troops into Lesotho. It focuses on the difficulty South African officials had in aligning their political objectives with the military exigencies of the rapidly changing crisis. This re-examination of the Lesotho intervention rectifies historical inaccuracies while also identifying potential problems that policy makers should be conscious of when considering future peace missions.